2021
DOI: 10.1093/geroni/igab030
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Making it CLEAR Questionnaire: A Resilience Measure for Older Adults

Abstract: Background and Objectives Previous efforts to develop a resilience measure for older adults have largely failed to consider the environmental influences on their resilience, and have primarily concentrated on the resilience of community dwelling older adults. Our objective was to validate a new multidimensional measure of resilience, the Making it CLEAR (MiC) questionnaire, for use with older adults at the point of discharge from hospital. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The results confirm that co‐morbidities negatively contribute to healthy ageing among older people who have an acute admission, while greater self‐efficacy and resilience positively contribute to healthy ageing. Self‐efficacy was also positively associated with resilience, supporting previous literature identifying self‐efficacy as a key determinant of resilience (Whitehall et al, 2021 ). This suggests that increasing self‐efficacy may have the benefit of not only promoting healthy ageing but also enhancing resilience among older people in acute hospital settings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results confirm that co‐morbidities negatively contribute to healthy ageing among older people who have an acute admission, while greater self‐efficacy and resilience positively contribute to healthy ageing. Self‐efficacy was also positively associated with resilience, supporting previous literature identifying self‐efficacy as a key determinant of resilience (Whitehall et al, 2021 ). This suggests that increasing self‐efficacy may have the benefit of not only promoting healthy ageing but also enhancing resilience among older people in acute hospital settings.…”
Section: Discussionsupporting
confidence: 83%
“…Self‐efficacy is an intrinsic or personal resource that contributes to factors associated with healthy ageing and resilience among older people (Remm et al, 2021; Whitehall et al, 2021). It is defined as a person's belief in their capability to perform at a level required to succeed in an event that affects their life (Bandura, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the main characteristics of the 38 included self-care measurement tools. The majority ( n = 26; 68.4%) of tools originated from North America (24 from USA, two from Canada) while the remaining originated from the UK (SFS [ 25 ], MiC questionnaire [ 26 ]), Norway (LSCS [ 27 , 28 ]), Spain (ASA-R [ 29 ]), Finland (SCHDE [ 30 ]), the Netherlands (ASA-A) [ 31 ] SeMaS [ 32 ]) and Italy (SCI – Patient Version [ 33 ]). Four tools, the EQ-5D [ 34 ], SASS-14 [ 35 ], SSCII [ 36 ] and the SASE [ 26 ] resulted from international collaborations.…”
Section: Resultsmentioning
confidence: 99%
“… Self-reported / Staff System: 1–6-Likert scale (1: strongly disagree to 6 > strongly agree) Total points: 0–100 (obtained through linear regression from the initial 10–60). Higher score indicates higher activation 35 Making it CLEAR (MiC) questionnaire [ 26 ] 2021 UK Multidimensional measure of resilience for use with older adults at the point of discharge from hospital. 34 items assess individual determinants of resilience (IdoR, 21 items) & environmental determinants of resilience (EdoR, 13 items).…”
Section: Resultsmentioning
confidence: 99%
“…With regards to community social capital, the results revealed that the effects of social cohesion were protective whereas social participation might increase fall risks. According to the person–environment fit theory, a harmonious social environment could enhance individual’s resilience ( Whitehall et al, 2021 ). However, social participation usually means venturing outside the home and facing more uncertainties, which easily increases the risk of falls.…”
Section: Discussionmentioning
confidence: 99%